PENANAMAN SOCIAL SKILLS DALAM PEMBELAJARAN IPS UNTUK MENCEGAH BULLYING PADA PESERTA DIDIK KELAS VII - Rezika Putri Mei Linda Prameswari; Yadi Suryadi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This study was motivated by the continued presence of bullying behavior among seventh-grade students at SMP Negeri 15 Semarang, including verbal, social, physical, and cyberbullying, which is linked to the students’ low social skills. The study aims to examine the implementation of social skills development in social studies instruction to prevent bullying, the integration of social skills into the social studies learning process, as well as the supporting and inhibiting factors. The study employed a qualitative approach using a case study design. Data were collected through participant observation, in-depth interviews, and documentation with informants including Social Studies teachers, guidance counselors, and seventh-grade students from classes VII C and VII E. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions using the Miles and Huberman model. The results of the study indicate that social studies teachers have implemented various learning strategies, such as group discussions, role-playing, Problem-Based Learning (PBL), and a personalized approach, to instill social skills in students. The development of social skills is also integrated into the planning, implementation, and evaluation of social studies instruction through materials related to everyday social life. This implementation has a positive impact on communication skills, cooperation, empathy, and responsibility, as well as reducing bullying behavior in the school environment. Supporting factors for this study include school culture, anti-bullying programs, and teacher involvement, while inhibiting factors include time constraints, differences in student personalities, lack of family support, and the influence of the environment outside of school. ABSTRAK Penelitian ini dilatarbelakangi oleh masih adanya perilaku bullying pada peserta didik kelas VII di SMP Negeri 15 Semarang, seperti bullying verbal, sosial, fisik, maupun cyberbullying yang berkaitan dengan rendahnya keterampilan sosial peserta didik. Penelitian ini bertujuan untuk mengetahui implementasi penanaman social skills dalam pembelajaran IPS untuk mencegah bullying, integrasi social skills dalam proses pembelajaran IPS, serta faktor pendukung dan penghambatnya. Penelitian menggunakan pendekatan kualitatif dengan jenis studi kasus. Data diperoleh melalui observasi partisipatif, wawancara mendalam, dan dokumentasi dengan informan guru IPS, guru BK, dan peserta didik kelas VII C dan VII E. Analisis data dilakukan melalui tahap reduksi data, penyajian data, dan penarikan kesimpulan menggunakan model Miles dan Huberman. Hasil penelitian menunjukkan bahwa guru IPS telah menerapkan berbagai strategi pembelajaran seperti diskusi kelompok, role play, Problem Based Learning (PBL), dan pendekatan personal untuk menanamkan keterampilan sosial peserta didik. Penanaman social skills juga diintegrasikan dalam perencanaan, pelaksanaan, dan evaluasi pembelajaran IPS melalui materi yang berkaitan dengan kehidupan sosial sehari-hari. Implementasi tersebut memberikan dampak positif terhadap kemampuan komunikasi, kerja sama, empati, tanggung jawab, serta mengurangi perilaku bullying di lingkungan sekolah. Faktor pendukung penelitian ini meliputi budaya sekolah, program anti-bullying, dan keterlibatan guru, sedangkan faktor penghambatnya yaitu keterbatasan waktu, perbedaan karakter peserta didik, kurangnya dukungan keluarga, dan pengaruh lingkungan luar sekolah.